Isolation and cloning of sesquiterpene synthases (amgs3 and amgs4) and chalcone synthase (amchs) from aquilaria malaccensis responsible for agarwood formation - Aimi Wahidah, Aminan; Siti Zulaiha, Zainol; Saiful Nizam, Tajuddin; Ramli, Aizi Nor Mazila (Malaysian Institute of Chemistry, 2021)
Sesquiterpene and phenylethyl chromone, two types of agarwood marker compounds, have been extensively studied. However, genetic studies of agarwood (Aquilaria malaccensis) are still scarce. This study describes the isolation and cloning of sesquiterpene synthase genes (AmGS3 and AmGS4), and chalcone synthase gene (AmCHS) identified from A. malaccensis transcriptome data mining. The sizes of AmGS3, AmGS4, and AmCHS were 1162, 1466, and 1623 bp in length. The open reading frames (ORFs) of AmGS3, AmGS4, and AmCHS detected were 948, 1047, and 1185 bp, with a polypeptide length of 348, 315, and 394 amino acids. The full-length sequences of AmGS3, AmGS4, and AmCHS were successfully isolated from the infected stem of A. malaccensis, amplified via polymerase chain reaction (PCR), cloned into the pGEM-T Easy Vector, and transformed into prepared Escherichia coli DH5a competent cells. The sequencing result and BLASTn analysis revealed that the ORFs of AmGS3 and AmGS4 are highly homologous to putative delta-guaiene synthase from Aquilaria sinensis, with a similarity of 98.1% and 98.08% respectively, while the ORF of AmCHS is highly homologous to chalcone synthase from A. sinensis with a similarity of 99.24%. These results demonstrated the successful isolation of sesquiterpene synthase and chalcone synthase genes that may play important roles in forming agarwood sesquiterpene and phenylethyl chromone in A. malaccensis.